A Novel Simulink-Based Implementation of Cosine Comparator Logic for Gate Control in Three-Phase Controlled Rectifiers - Annisa, Selly; Immanuel, Michael Fritz; Pratama, Saras; Ashari, Muhammad; Saragi, Dian Putra (Techno.Com, 2025)
This paper proposes a cosine comparator-based firing angle control strategy for three-phase full-wave thyristor rectifiers. Gate pulses are generated by comparing phase-synchronized cosine reference signals with a tunable threshold voltage, allowing precise control over conduction intervals. The method’s effectiveness is evaluated across firing angles ranging from 30° to 120° under RLC load conditions. Quantitative results demonstrate accurate gate synchronization and substantial reduction in Total Harmonic Distortion (THD)—by over 50% relative to conventional ramp-based techniques. The findings confirm the proposed control scheme's potential for high-performance, low-distortion AC-DC conversion, making it suitable for industrial and educational power electronics applications.   Keywords - Three-phase controlled rectifier, cosine comparator, firing angle, Simulink modeling, thyristor gate control, FFT analysis.